Sosialisasi Pengelolaan Limbah B3 Pada Kegiatan Sekolah dan Otomotif di Sekolah Menengah Kejuruan - Wicaksono, Surya Adi; Kartika, Wahyu; Masrida, Reni Masrida; Hasaya, Haudi; Meilani, Sophia Shanti (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2025)
Hazardous and Toxic Waste (B3) is a significant contributor to environmental pollution and requires proper management in accordance with regulatory standards. In vocational education, particularly automotive programs at Vocational High Schools, workshop activities commonly generate B3 waste such as used oil, batteries, and chemical containers. To address this issue, the Environmental Engineering Study Program of Universitas Bhayangkara Jakarta Raya conducted a community service program at Panca Bhakti Banjarnegara focused on B3 waste management. The activity was carried out through presentations and a Focus Group Discussion (FGD), covering the identification, temporary storage, and further handling of B3 waste based on Ministry of Environment and Forestry Regulation No. 6 of 2021 and Government Regulation No. 22 of 2021. The results showed an increase in participants’ understanding regarding regulatory obligations, proper storage practices, and the importance of preventing environmental pollution at the school scale. In conclusion, this program effectively strengthened knowledge and awareness of environmentally responsible practices, while laying the foundation for ongoing collaboration between the school and university. The program is expected to support the development of environmentally conscious graduates who are prepared to manage B3 waste responsibly in future industrial or automotive workplace settings.